2022
DOI: 10.1155/2022/5680170
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cortisol, 25 (OH)D, and Cardiovascular Risk Factors in Patients with Type 2 Diabetes Mellitus

Abstract: Background and Aims. The effects of cortisol on cardiovascular diseases (CVD) and CVD risk are unknown, especially in patients with type 2 diabetes mellitus (T2DM). Furthermore, it is unclear whether 25 (OH)D can alter the associations of cortisol with CVD and CVD risk factors. Thus, the present study was to investigate the associations of serum cortisol with CVD and CVD risk factors and whether 25 (OH)D altered these associations among patients with T2DM. Materials and methods. A total of 762 patients diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
3
0
1
Order By: Relevance
“…Cortisol is an important product of the steroid hormone biosynthetic pathway and is considered an active indicator of the Hypothalamic-pituitary-adrenal(HPA)axis. A recent study has shown that cortisol is associated with dyslipidemia and impaired glucose metabolism [25]. Desulfovibrio has been reported to be negatively correlated with γ-aminobutyric(GABA) [26], which can inhibit glucagon secretion and enhance insulin secretion [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol is an important product of the steroid hormone biosynthetic pathway and is considered an active indicator of the Hypothalamic-pituitary-adrenal(HPA)axis. A recent study has shown that cortisol is associated with dyslipidemia and impaired glucose metabolism [25]. Desulfovibrio has been reported to be negatively correlated with γ-aminobutyric(GABA) [26], which can inhibit glucagon secretion and enhance insulin secretion [27].…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol is an important product of the steroid hormone biosynthetic pathway and is considered an active indicator of the hypothalamic-pituitary-adrenal (HPA) axis. A recent study has shown that cortisol is associated with dyslipidemia and impaired glucose metabolism [29]. Desulfovibrio has been reported to be negatively correlated with γ-aminobutyric acid (GABA) [30], which can inhibit glucagon secretion and enhance insulin secretion [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on BDNF rs2049046 polymorphisms focus on migraine, and the A allele carriers have lower morbidity, 45 which is associated with higher cortisol level, especially for epinephrine corticoids 46 . Given that elevated cortisol level was related to cardiovascular risk factors, including deceased β‐cell function and increased triglycerides, 47 leading to cardiovascular homeostatic load and thus resulting in higher cardiovascular susceptibility in patients with the BDNF rs2049046 A genotype.…”
Section: Discussionmentioning
confidence: 99%